Development of Social and Culture Aspects Pre-service Science Teachers on Learning for Nature of Science - Euis Nursa'adah; Bhakti Karyadi; Ratu Eva Febriani; Ahmad Mudzakir (Postgraduate, University of Mataram, 2022)
Understanding aspects of the Nature of Science (NOS) for preservice science teachers is one of the essential components to be able to understand Science and its processes. There are seven aspects of NOS: empirical, inference, creative, latent theory, tentative, scientific procedural myths, theories and laws of science, social and cultural dimensions, and their embedding in science. There are 48 preservice science teachers involved in this study. Researchers explored their views about NOS and Indigenous Knowledge (IK) through a validated questionnaire. Results showed that the students' opinions on NOS consisted of empirical, tentative, inference, law, scientific theory, and creativity. Meanwhile, aspects of laden theory, myths of scientific procedures, and social and cultural dimensions embedded with science have not been described by students. Fortunately, the students presented IK as an authentic context based on the culture in science learning.Â Students express IK ideas: 1) biomedicine (40 students), Biopesticide (2 students), beauty ingredients (2 students), additives (1 student), and supernatural medicine (1 student). Integrating Science and IK as an authentic context in science learning leads IK toward high technology and strengthens NOS aspects. In addition, the assumption that IK has no future is declining.